2018
DOI: 10.1111/sdi.12694
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis‐induced cardiovascular disease

Abstract: More than half of all deaths among end stage renal disease (ESRD) patients are due to cardiovascular disease (CVD). Cardiovascular changes secondary to renal dysfunction, including fluid overload, uremic cardiomyopathy, secondary hyperparathyroidism, anemia, altered lipid metabolism, and accumulation of gut microbiota-derived uremic toxins like trimethylamine N-oxidase, contribute to the high risk for CVD in the ESRD population. In addition, conventional hemodialysis (HD) itself poses myocardial stress and inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 120 publications
(213 reference statements)
4
100
0
3
Order By: Relevance
“…We found that a longer hemodialysis vintage was associated with a higher healthcare cost. This can be explained by the fact that long-term dialysis patients possibly required more treatments, or experienced more complications [ 48 , 49 , 50 , 51 ], which, in turn, increased the treatment burden [ 52 ]. Comorbidities were associated with a higher healthcare cost in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a longer hemodialysis vintage was associated with a higher healthcare cost. This can be explained by the fact that long-term dialysis patients possibly required more treatments, or experienced more complications [ 48 , 49 , 50 , 51 ], which, in turn, increased the treatment burden [ 52 ]. Comorbidities were associated with a higher healthcare cost in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, end‐stage CKD patients treated with hemodialysis are considered to be at very high cardiovascular risk that is related both to an increased prevalence of traditional cardiovascular risk factors and the effects of CKD‐related factors (ie, dialysis per se, periodic volume overload, uremia, chronic inflammation and increased oxidative stress, mineral disorders, anemia, etc) . In hemodialysis patients, atherosclerotic changes, calcifications, and impaired coronary endothelial function may lead to coronary microvascular and epicardial vascular dysfunction and consequently to chronic myocardial ischemia . Increased aortic stiffness is also very common in these patients and may also contribute to impaired left ventricular function and myocardial ischemia …”
Section: Introductionmentioning
confidence: 99%
“…However, despite the advances in hemodialysis technology, the mortality and morbidity of ESRD patients on MHD remains high and the quality of life of these patients is poor [2]. Cardiovascular disease is a major complication of ESRD that is caused by metabolic and hemodynamic changes due to ESRD and is associated with high mortality [3,4], accounting for approximately 50% of hemodialysis patient deaths [5]. Left ventricular (LV) dysfunction is a critical indicator of cardiac dysfunction and an early clinical manifestation of LV hypertrophy.…”
Section: Introductionmentioning
confidence: 99%